Спосіб і засоби вчинення незаконного полювання як обставини доказування у кримінальному провадженні (на матеріалах судової практики) - Горбунова, К. В.; Horbunova, K. V.; Катерина Горбунова (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 2. - С. 213-223, 2023)
Проведено аналіз практики застосування норми про відповідальність за незаконне полювання (ст. 248 Кримінального кодексу України), виявлено найбільш поширені способи та знаряддя (засоби) незаконного полювання. На підставі дослідження визначено типове поєднання способів і знарядь (засобів) незаконного полювання.

The present criminal and criminal procedural legislation, as well as the practice of application of the provisions on criminal liability for illegal hunting have been studied. As the study subject, the examples of case law have been chosen, which allowed to identify typical ways and means of committing a criminal offence in the presence of specific circumstances of their application. The correlation of substantive and procedural law provisions aimed at achieving the goal and fulfilling the tasks of investigating criminal offences against the environment has been analysed; recommendations on the practice of application of criminal liability provisions have been provided; the correct interpretation of the ways and means of committing illegal hunting based on the analysis of law enforcement practice has been ensured. Based on the analysis of law enforcement practice of some aspects of the criminal procedural component, the most common and typical means, methods (forms), and tools of illegal hunting used in encroachment on wildlife have been identified. It has been established that preparation for committing illegal hunting may include: choosing the time and place of illegal hunting; searching for and preparing illegal hunting tools and means; selection of accomplices to illegal hunting; and deciding on the prey. The typical ways of committing illegal hunting have been defined as follows: hunting without a permit (for hunting animals, for the use of firearms, etc.); hunting at prohibited times (during the periods prohibited for hunting of the respective species of animals, in the dark, etc.); hunting with the use of prohibited tools and prohibited methods (nooses, traps, nets, etc.); hunting in prohibited areas (on the territories and objects of the nature reserve fund, in reproduction areas, etc.); hunting for animal species listed in the Red Book. The above list of typical methods and tools for committing illegal hunting is not exhaustive, but is the most promising in terms of developing methods for their investigation. The most common tools used in illegal hunting are hunting (smoothbore or firearms) weapons, nooses and nets.

Проведен анализ практики применения нормы об ответственности за незаконную охоту (ст. 248 Уголовного кодекса Украины), выявлены наиболее распространенные способы и орудия (средства) незаконной охоты. На основании исследования определено типичное сочетание способов и орудий (средств) незаконной охоты.
Methods and means of committing illegal hunting as circumstances of proof in criminal proceedings (based on case law)
Keywords: полювання; розслідування; кримінальне правопорушення; спосіб учинення правопорушення; засоби та знаряддя правопорушення; hunting; investigation; criminal offence; method of committing an offence; means and tools of an offence; охота; расследование; уголовное правонарушение; способ совершения правонарушения; средства и орудия правонарушения